2006
DOI: 10.1007/s11064-006-9147-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of GD3-Induced Apoptosis in U-1242 MG Glioma Cells

Abstract: An increasing amount of evidence indicates that the disialoganglioside GD3 is involved in apoptosis in many cell lines. Our previous studies demonstrated that endogenous GD3 expression induced apoptosis in U-1242 MG glioma cells transfected with the GD3 synthase gene (U1242MG-GD3 cells). In this paper, we present further investigations on the molecular mechanisms of GD3-induced apoptosis in this cell line. We found that endogenously synthesized GD3 localizes to the caveolae of this cell line, where it promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…In other studies, an important role of membrane-associated ASMase was suggested in Fas-mediated apoptosis as activation of ASMase leads to the generation of free ceramide, which then can be converted to GD3 (60, 61). A similar pathway has been recently described in TNFα-mediated apoptosis (62, 63). Significant 9- O -acetyl GD3 accumulation, together with increases in GM2 and GM4 gangliosides in glomerular cells was also observed after low level and long term lead exposure and was associated with decreased apoptosis in glomerular cells suggesting that GD3-O acetylation could represent a new strategy to attenuate apoptosis in renal glomerular cells and contribute to cell survival as observed during lead exposure (64).…”
Section: Sphingolipid Accumulation and Glomerular Disease Of Genetic supporting
confidence: 71%
“…In other studies, an important role of membrane-associated ASMase was suggested in Fas-mediated apoptosis as activation of ASMase leads to the generation of free ceramide, which then can be converted to GD3 (60, 61). A similar pathway has been recently described in TNFα-mediated apoptosis (62, 63). Significant 9- O -acetyl GD3 accumulation, together with increases in GM2 and GM4 gangliosides in glomerular cells was also observed after low level and long term lead exposure and was associated with decreased apoptosis in glomerular cells suggesting that GD3-O acetylation could represent a new strategy to attenuate apoptosis in renal glomerular cells and contribute to cell survival as observed during lead exposure (64).…”
Section: Sphingolipid Accumulation and Glomerular Disease Of Genetic supporting
confidence: 71%
“…Omran and colleques described an involvement of GD3 in apoptosis in U-1242 glioma cells [24]. Zeng et al [25] found evidence for an association between GD3 Ganglioside and tumor progression and even development of metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…This supports our data, showing that upon pharmacological inhibition of APT2, TNF-R1 stays at the PM (putatively in caveolae) and induces ceramide production via nSMase in U937 cells. The Yates group showed that TNF-R1, CD95, and DR5 are located in caveolin-1 positive DRM fractions of U-1242 glioma cells by default and that TRAIL treatment invoked caspase-8 recruitment and activation in this compartment [ 49 , 50 ]. D’Alessio et al suggested a TNF-R1-membrane-proximal sequence, close to C248, as we recently reported, targeting it to caveolae and that TNF-R1 internalization requires caveolae localization [ 51 ].…”
Section: Roles Of Palmitoylation and Lipid Rafts In Tnf-r1 Signalingmentioning
confidence: 99%